Design, preparation and performance of a novel drug-eluting stent with multiple layer coatings. (5th July 2017) - Hu, Tingzhang; Lin, Song; Du, Ruolin; Fu, Meiling; Rao, Qiong; Yin, Tieying; Huang, Yan; Wang, Guixue
Abstract : A novel drug-eluting stent with multiple layer coatings could effectively inhibit intimal hyperplasia of rabbit carotid arteries after implantation. Abstract : Drug-eluting stents (DESs) can effectively control the harmful effects of coronary artery disease, because of their excellent ability to reduce in-stent restenosis. However, delayed re-endothelialization and late stent thrombosis have caused concern over the safety of DESs. In this study, according to time-ordered pathological responses after stent implantation, a hierarchical multiple drug-eluting stent was designed and prepared to overcome the existing DES limitations. A platelet membrane glycoprotein IIIa monoclonal antibody (SZ-21) and a vascular endothelial growth factor (VEGF121 ) were loaded into the inner coating of 316L stainless steel (316L SS) stents to inhibit thrombosis and promote re-endothelialization; rapamycin (RAPA) was loaded into the third layer to inhibit intima hyperplasia; a drug-free poly-l -lactic acid coating was located on the second and fourth layers and used as sustained release layers. The results showed that the three drugs exhibited sequential release kinetics without significant burst release. RAPA released quickly at the early stage, while SZ-21 and VEGF121 achieved a slow and prolonged release. In vitro experiments showed that the stents had excellent hemocompatibility and anti-inflammatory properties, and promoted the proliferation and migration of endothelial cells while inhibiting the proliferation and migration of smooth muscle cells. Finally the stents were implanted in the carotid arteries of New Zealand white rabbits. In vivo results showed that compared to 316L SS stents, the multiple drug-eluting stents could accelerate re-endothelialization and inhibit thrombosis, inflammation and in-stent restenosis after 4 weeks (12.79 ± 2.45% vs . 25.27 ± 4.81%) and 12 weeks (15.87 ± 3.62% vs . 58.84 ± 6.87%). These results indicate that the novel drug-eluting stent with multiple layer coatings will have a highly potential clinical application.